Animal Sperm Freezing Under Laboratory and Field Conditions - Gorbunov, L. V.; Salina, A. S. (Problems of Cryobiology and Cryomedicine, 2006)
The device for cryopreservation of sexual cells of mammalians and fish under field conditions has been proposed. It provides freezing rates from 0.5 to 30ÂºC/min. The change in freezing rate is achieved with dosed intensity of heat-conducting path by means of â€œmantelâ€ from metal container with biological object in X-35 Dewar vessel neck. Location of containers with biological objects in precooled thermal block helps to realize various behaviors of rate changes. Using the methods of mathematical modeling there have been chosen the materials and parameters of metal container providing minimum gradient of temperature distribution (â‰¤1ÂºC/cm) during cooling that provides freezing of cell suspensions up to 5 ml in a container. The height location of â€œmantelâ€ regarding metal container and depth of its submerging into X-35 Dewar vessel neck, necessary to realize optimal freezing regimens of bovine and fresh-water fish sperm have been established. Survival of frozen-thawed carp sperm made 45 and 40% for bovine ones.